Strength training effects of whole-body vibration? - Nordlund, M. M.; Thorstensson, A. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Whole-body vibration (WBV) has been suggested to have a beneficial effect on muscle strength. Manufacturers of vibration platforms promote WBV as an effective alternative or complement to resistance training. This study aimed to review systematically the current (August 2005) scientific support for effects of WBV on muscle strength and jump performance. MEDLINE and SPORT DISCUS were searched for the word vibration in combination with strength or training. Twelve articles were included in the final analysis. In four of the five studies that used an adequate design with a control group performing the same exercises as the WBV group, no difference in performance improvement was found between groups, suggesting no or only minor additional effects of WBV as such. Proposed neural mechanisms are discussed.